Peningkatan Keterampilan Guru Kimia Melalui Pembuatan Modul Praktikum Berbasis Problem Based Learning - Maria Erna Maria; Johni Azmi; Sri Wilda Albeta (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The skills of chemistry teachers in Rambah Hilir upstream of Rokan Hulu Regency can be improved through training in the making of chemistry practicum modules based on Problem Based Learning (PBL). Without chemistry practicums it will be difficult to learn and will be a scary lesson for students in school. For this reason chemistry teachers are needed who are skilled in making practicum modules. In this service, socialization, training and coaching have been conducted so that teachers can independently create PBL-based chemistry practicum modules. The results of the activity showed that the perception of the trainees was good, namely that 81.25% of the attitudes of the participants were categorized Very High and 18.75% were categorized as High. Participants in this activity showed enthusiasm and activeness, mastery of the material, creativity, use of language and ways of conveying ideas still need guidance. Participants have successfully created a chemical practicum module with the subject of electrical conductivity, how to separate the mixture and test the food properly. This service is important so that teachers can apply the 2013 curriculum with a scientific approach.